Jigsaw in teaching circulatory system: a learning activity on elementary science classroom - Leasa, Marleny; Sanabuky, Yakub Lalyolik; Batlolona, John Rafafy; Enriquez, Javier Julia (Biosfer: Jurnal Pendidikan Biologi, 2019)
Jigsaw type cooperative learning is explored again to train students from an early age to become a small expert to reveal the effects it has on the cognitive achievement of elementary students. The study was conducted at one of the public schools in Ambon City, preceded by a placement test on the classes used. The cognitive learning achievement test instrument was developed with a cognitive load reaching C4 and has met the instrument quality prerequisite tests. The results of the study prove that there are differences in student learning outcomes in learning with Jigsaw and Example Non-Example (ENE) types. The corrected mean score showed that the treatment group was 25,856 points higher than the control group. This means that Jigsaw is superior in improving student cognitive achievement compared to ENE. Thus, Jigsaw can be used in other learning in elementary school because it has the potential to enhance student learning outcomes. Further studies are needed to uncover the potential of Jigsaw to empower various types of learning outcomes and other thinking skills.